Tribological properties of hybrid surface textured GCr15 steel filled by epoxy resin-based material under dry friction. (28th May 2019) - Jiang, Shiyu; Li, Jinbang; Liu, Shuo; Zhou, Ningning; Yu, Aibing; Deng, Yimin
Abstract: Micro-grooves were fabricated on GCr15 steel disc and filled by epoxy resin composites, formed hybrid laser surface texture. The tribological properties of textured disc sliding against ceramic ball were investigated. The friction tests were carried on a ball-on-disc tribometer. Three kinds of fibers, two kinds of particle and three kinds of polymer were selected to improve the epoxy resin-based material filled in the micro-grooves. Glass fiber (GF), graphite particle (GP) and PTFE shown better tribological performances, which were selected as additives for the optimized design of the epoxy resin composite. The specimen with fill ratio of 3:1:1 (PTFE: GF: GP) exhibits lower friction coefficient and better wear resistance. The worn surface of textured discs and balls were observed. It was found that this hybrid laser surface texture could form a transfer layer on the contact surface, which contribute to the friction and wear reduction of tribo-pairs under dry friction condition.